Is the European Semester effective and useful? - Konstantinos Efstathiou; Guntram B. Wolff (Bruegel, 2018)
We study whether and to what extent EU countries implement recommendations on macroeconomic imbalances given by the EU in the so-called European Semester. We assess how recommendations have evolved since 2013, based on a new database. We also study how EU recommendations on addressing macroeconomic imbalances compare to recommendations given by the International Monetary Fund. Overall implementation of recommendations by EU countries has worsened in the last few years, in particular when it comes to recommendations addressed to countries with excessive macroeconomic imbalances. The policy content of the recommendations is broadly aligned with economic priorities emphasised by their corresponding legal bases, but to our surprise a sizable share of recommendations, such as on childcare, are also labelled as relevant for resolving macroeconomic imbalances. Moreover, for countries with macroeconomic imbalances, the IMF tends to emphasise financial imbalances more frequently than the EU. We also note that the EU makes significant political choices about which imbalances are judged to be excessive and which are judged not excessive. Low implementation is likely a result of the fundamental dilemma facing the EU. National policies have major cross-border implications making coordination important, but countries take sovereign decisions mostly based on national considerations. We therefore argue that recommendations given in the context of macroeconomic imbalances should be focused on key issues of macroeconomic and cross-border relevance. Moreover, we note a significant gap between analyses as described in the recitals of recommendations and the actual recommendations, and would urge greater consistency. Finally, the European Semester exercise is very difficult to digest and communication of key analyses and recommendations could be significantly improved to make them more accessible to national policymakers.
Keywords: 330